2011
DOI: 10.1007/s00431-010-1386-1
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroid disease in Libyan children and young adults with type 1 diabetes mellitus

Abstract: The prevalence of autoimmune thyroid disease in type 1 diabetic patients is higher than in the general population. A routine screening strategy should be implemented with the determination of anti-thyroid antibodies and TSH in type 1 diabetic patients, particularly in girls, and in patients with diabetes of more than 5 years duration. Patients who have positive TPO antibodies may need the assessment of thyroid function at shorter intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
5
29
3
Order By: Relevance
“…The prevalence reported and study sample size varied from one study to another study. The prevalence of subclinical hypothyroidism was reported as 2.3 times in adult population of Libya (Ghawil et al, 2011) compared with study conducted in Colorado documented that the prevalence of subclinical hypothyroid in the general population ranged between 4 and 10% (Canaris et al, 2000). So, our review suggested that the prevalence in Arab region is comparatively low.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The prevalence reported and study sample size varied from one study to another study. The prevalence of subclinical hypothyroidism was reported as 2.3 times in adult population of Libya (Ghawil et al, 2011) compared with study conducted in Colorado documented that the prevalence of subclinical hypothyroid in the general population ranged between 4 and 10% (Canaris et al, 2000). So, our review suggested that the prevalence in Arab region is comparatively low.…”
Section: Discussionmentioning
confidence: 49%
“…The review results showed different study designs as follows: seven cross-sectional studies were conducted in different Arab regions, including Libya, Saud Arabia, Egypt, Algeria, Bahrain and Oman (El-Mougi et al, 2004;Ghawil et al, 2011;Henjum et al, 2010;Lamfon, 2008;Moosa et al, 2000;Nouh et al, 2008;Elbualy et al,1998). The sample size found varied from 99 to 749 subjects except for one study conducted in Oman in which 36000 babies were diagnosed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid autoimmunity is increased in females and with longer duration of diabetes (2,12,37,54). Prospective follow-up showed that the development of thyroid disease was related to the female gender and the presence of TPO antibodies, and measuring of circulating antibodies against thyroid peroxidase (anti-TPO Ab) and thyroglobolin (antiTg Ab) can be made easily (70).…”
Section: Discussionmentioning
confidence: 99%
“…Type one diabetes mellitus (T1DM) is an autoimmune disorder that is yet the most common type of diabetes in children and adolescents (1,2). This disorder results from immune and non-immune destruction of β-cell islets of the pancreas (3).…”
Section: Contextmentioning
confidence: 99%